D’DAUN / Azwa Natasha Ahmad Jaflus - Ahmad Jaflus, Azwa Natasha; Shamsul Adli, Fadzlina Adleen; Rosli, Maryam Irdina; Faisol, Miza Syahirah Alwi; Syed Nusyadir, Sharifah Nazira (2021)
A business plan can be defined as a detailed document that describes the business concepts and strategies to achieve the business objectives. The purpose of our business plan is to produce a sustainable product, promote the product locally and fulfil the demand for this certain type of clothing. In this business plan, we state the details of our company, business competition, and who are our customers to make it easier for readers to read the entire business plan. Our company, D'DAUN provides a variety of products and services through our brand which follows the development of fashion trends and market changes. We encourage innovation and creativity in producing fresh new ideas for our designs that also give a positive impact to society. D’DAUN is located in SACC mall, Shah Alam, Selangor. Our main product is upcycled clothes but we also provide custom design service to customer within their budget. In this case, customers can choose and design their own ideas according to their own tastes and preferances. Even though there are many competitors, there still a lot of demand from customer for more affordable custom clothing. The target audience for D’DAUN is The Youths group which currently make up 45% of the population in Malaysia. The Youth are categorised as people aged 15 to 39 years old that are either in school, university or in the working sector. This group is one of the largest groups in Malaysia and has the potential to become a small business buyer. D’DAUN’s objective is to be able to market sustainable clothing worldwide while simultaneously spreading awareness to the community emphasizing on not throwing away old clothes by transforming it into newer, more in-trend, eco-friendly clothing. With the younger generation being more interested in advocationg for a cleaner and more sustainability in the fashion industry, we feel that our company is uniquely positioned to profit from the consumers change in opinion. We also feel that our company can continue to leverage the expertise we have gained to continuously profit and maintain customer satisfaction.